PerioVax3, a key antigenic determinant with immunoprotective potential against periodontal pathogen. (October 2019) - Hashemi, Saba; Sepehrizadeh, Zargham; Setayesh, Neda; Kadkhoda, Zeinab; Faramarzi, Mohammad Ali; Shahverdi, Ahmad Reza; Glogauer, Michael; Amin, Mohsen
Abstract: Treponema ( T. ) denticola is one of the key etiological agents in the development of periodontitis. The major outer sheath protein (Msp) of T. denticola has been shown to mediate pathogenesis and to facilitate adhesion of T. denticola to mucosal surfaces. This study aimed to find short polypeptides in the amino acid sequence of Msp which may be immunogenic and might elicit protective antisera against T. denticola . The complete msp sequence was divided into six fragments and the corresponding genes were cloned and expressed. Antisera against the polypeptides were raised in rabbits and fragment 3 (F3), hereinafter called PerioVax3 was the most potent fragment of the Msp in terms of yielding high titer antiserum. An adhesion assay was done to examine the inhibitory effects of antisera on the attachment of T. denticola to human gingival fibroblasts (HGFs) and human fibronectin. Antiserum against PerioVax3 significantly inhibited attachment of T. denticola to the substratum. Also, antiserum against PerioVax3 inhibited detachment of HGFs upon T. denticola exposure. To begin examining the clinical relevance of this work, blood samples from 12 sever periodontitis patients were collected and the sera were used in western blotting against the recombinant polypeptides. Periodontitis patient antisera exclusively detected PerioVax3 in western blotting. The data suggest that PerioVax3 carries epitopes that may trigger humoral immunity against T. denticola, which may protect against its adhesion functions. The complexity of periodontitis suggests that PerioVax3 may be considered for testing as a component of an experimental multivalent periodontal vaccine in further preclinical and clinical studies. Highlights: PerioVax3 was the most immunogenic fragment of Treponema (T.) denticola Msp. Antiserum against PerioVax3 inhibited adhesion of T. denticola . Periodontitis patient antisera exclusively reacted with PerioVax3 . Antiserum against PerioVax3 inhibited detachment of human gingival. PerioVax3 may constitute periodontal vaccine potential.